OFR 74-78 - Waveform Generator-Package And Receiver (Mancarried And Helicopter Receiver Portion) - Charles Anema (The National Institute for Occupational Safety and Health (NIOSH), 1976)
The Mancarried and Helicopter Receivers were developed under the contract I for trapped miner location. This program was a five phase program with 15 mancarried and 5 helicopter production receivers delivered under Phase IV and equipment documentation required under Phase V.